HARMONI NILAI-NILAI PANCASILA DALAM AGAMA HINDU - Puspo Renan Joyo (Fakultas Dharma Duta, 2017)
Pancasila is the foundation and ideology of the state. It is a formula consisted of the essences of the values of customs, cultures, and religions which are highly valued by the Indonesian people. Radicalism, terrorism, religious intolerance, and the attempts to push religion as a new ideology is an anomalous phenomenon against the spirit of Pancasila. There is a problem of understanding of the values of Pancasila from religious perspective. This paper aims at tracking the values of Pancasila in Hinduism, as an effort to correlate the values of Pancasila with Hinduism. The theoretical frameworks and analysis used to help decipher the discussion of this paper were semiotics and content analysis. The results show that the values of Pancasila are in harmony with the values contained in the teachings of Hinduism, such as Godly values, religious tolerance, humanism and brotherhood, unity in diversity, deliberation, and social justice.